2008
DOI: 10.1007/s00705-008-0164-0
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic characterization of bovine ephemeral fever rhabdovirus G and GNS glycoproteins expressed from recombinant baculoviruses

Abstract: Recombinant baculoviruses expressing the BEFV envelope glycoprotein G and non-structural glycoprotein G(NS) were constructed. The G protein expressed in insect cells was located on the cell surface and induced spontaneous cell fusion at mildly acidic pH. The expressed G protein reacted with MAbs to continuous and conformational neutralization sites (G1, G2, G3b and G4), but not to conformational site G3a. The expressed G(NS) protein was also located on the cell surface but did not exhibit fusogenic activity. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…While one of the sites (G1) reacts only with anti-BeFV antibodies, the others (G2 -G4) show crossreactivity with sera against other related viruses (CYBINSkI et al, 1990;CYBINSkI et al, 1992;JOhaL et al, 2008;kONGSUWaN et al, 1998). the composition of these regions in the G gene sequences of the 2012-BEFVs differed from that of other field viruses from the 1985 and 2008 outbreaks in turkey.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…While one of the sites (G1) reacts only with anti-BeFV antibodies, the others (G2 -G4) show crossreactivity with sera against other related viruses (CYBINSkI et al, 1990;CYBINSkI et al, 1992;JOhaL et al, 2008;kONGSUWaN et al, 1998). the composition of these regions in the G gene sequences of the 2012-BEFVs differed from that of other field viruses from the 1985 and 2008 outbreaks in turkey.…”
Section: Discussionmentioning
confidence: 91%
“…Glycoprotein G, which is one of the nonstructural proteins of the virus includes four distinct antigenic sites (G1 -G4) on its surface, and is considered the major neutralising and protective antigen of BeFV (JOhaL et al, 2008;UreN et al, 1984). While one of the sites (G1) reacts only with anti-BeFV antibodies, the others (G2 -G4) show crossreactivity with sera against other related viruses (CYBINSkI et al, 1990;CYBINSkI et al, 1992;JOhaL et al, 2008;kONGSUWaN et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The expressed G1 protein in a prokaryotic system, E. coli, had appropriate reaction activity and specificity with an anti-BEFV serum in immunoblot analysis (Zheng et al, 2007a;Beygi Nassiri et al, 2016). Johal et al (2008) showed that the expressed BEFV glycoprotein G by recombinant baculoviruses reacted with BEFV-neutralising monoclonal antibodies (MAbs) to all continuous and conformational antigenic sites and may be a useful vaccine antigen. Vaccinated rabbits and cattle with recombinant vaccinia viruses expressing the glycoprotein G developed high level of antibodies which neutralised BEFV in either mammalian or insect cells (Uren et al, 1994;Hertig et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The BEFV G glycoprotein is the target of virus neutralising antibodies (Cybinski et al, 1992;Uren et al, 1994). In addition, the highly protective characteristics of the native BEFV G protein suggest that its recombinant expressed product may be a useful vaccine antigen (Johal et al, 2008). Accordingly, recombinant or DNA vaccine based on G protein may be an appropriate alternative for current vaccines (Uren et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…BEFV G protein comprises an N-terminal signal peptide (amino acid 1-12), a C-terminal transmembrane domain, and a cytoplasmic tail (amino acids 522-623). The native BEFV G protein present on the virion is 81 kDa but the recombinant G protein expressed in insect cells appears to be either 76 or 71 kDa (7). Four antigenic sites on the G protein (G1-G4) were well characterized by sequence analysis and protein mapping using specific monoclonal antibodies (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%